Pengaruh Komposisi Media Tanam Tanah Limbah Peti dan Pemberian Pupuk NPK Terhadap Pertumbuhan Tanaman Sansevieria (Sansevieria macrophylla) - Tengku Nurhidayah; Agung Satria Siregar; Muhammad Ali (Jurnal Zona, 2024)
Sansevieria macrophylla, commonly known as tongue-in-law plant is one of the horticultural plants that is widely cultivated as an ornamental plants. The research was conducted experimentally in a 3x3 factorial experiment using a completely randomized design (CRD) pattern consisting of two factors. The first factor is the composition of growing media (M) consisted of three kinds: M1= (2:1:1); M2 = (1:2:1); M3= (1:1:2). The second factor is NPK fertilizer (N) consisted of three dosages: N1= (0 g/plant); N2= 5 g/plant; N3= 10 g/plant. Results indicated that the interaction of planting media composition and NPK fertilizer dosage had no significant effect on all observed parameters. The combination of growing media composition (1:1:2) and the application of NPK fertilizer at a dose of 10 g/plant increased plant leaf length, leaf width, fresh weight, root volume and primary root length. The composition of growing media (1:1:2) increased leaf length, leaf width, fresh weight, root volume and primary root length. NPK fertilizer at a dose of 10 g/plant increased leaf length, leaf width, root volume and primary root length of S. macrophylla.